Pre-stroke physical activity in relation to post-stroke outcomes - linked to the International Classification of Functioning, Disability and Health (ICF): A scoping review - Adam Viktorisson; Malin Reinholdsson; Anna Danielsson; Annie Palstam; Katharina S. Sunnerhagen (Medical Journals Sweden, 2022)
Objective: This scoping review aims to identify how pre-stroke physical activity (PA) has been studied in relation to outcomes after stroke using the ICF framework. Methods: MEDLINE, CINAHL, Scopus, and grey literature databases were systematically searched from inception to March 15, 2021, with no language restrictions. Risk of bias was evaluated for all included studies. Identified outcome measures were linked to ICF components using linking rules, and the main findings were summarized. Results: Of 3664 records screened, 35 studies were included. The risk of bias was graded as moderate to critical for all studies. There were 60 unique outcome measures studied in relation to pre-stroke PA, covering the hyper acute to chronic phases of stroke recovery. Outcome measures linked to body functions were most common (n=19), followed by activities and participation (n=14), body structures (n=7), environmental factors (n=4) and personal factors (n=2). There were large differences in assessments of pre-stroke PA, and only one study analysed haemorrhagic cases separately. Conclusions: Pre-stroke PA has been studied in relation to all components in the ICF framework.  However, this review highlights the high risk of bias, heterogeneity in pre-stroke PA assessments, and the lack of information regarding haemorrhagic strokes in the current literature. lay abstract We used the International Classification of Functioning, Disability and Health (ICF) to categorise the outcome measures of 35 studies. The ICF includes the following domains of health: body functions, body structures, activities, participation, and environmental factors. We identified 60 outcome measures, covering all domains of the ICF. Most common were measures related to body functions such as stroke symptoms, cognition or respiratory function, and activities or participation, such as functional recovery and walking ability. Few studies evaluated personal and environmental factors. Most studies collected information on physical activity before the stroke after the stroke had occurred, and all studies used self-reported information which is problematic from a scientific point of view and can lead to erroneous results. Future studies are needed to determine the true impact of physical activity on outcomes after stroke.